Analisis Ciri Khas Pola Kehidupan Sosial Masyarakat Suku Donggo: Suatu Tinjauan Sejarah Sosial Budaya - Nurjannah, Nurjannah; Khotimah, Husnul; Sumiyati, Sumiyati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2017)
[Title: Analysis of Special Level Pattern of Social Life of Donggo People: A Review of Social and Cultural History] It has been done by analyzing the characteristics of the social life of the Donggo community in Bima District (a social history review) in the field of marriage, with the aim of describing, the characteristic pattern of the social life of the Donggo community in Bima District. The data were analyzed descriptively and qualitatively with the result that both the observation and the interview result were the characteristics of social life pattern of Donggo community in Bima district in the field of marriage which started from the process of cane cepe (Stereo Infant Sling), Sodi Angi (Engaged), Ngge'e Nuru (Living Together), Mbolo Weki (Deliberation/Mufakat), Wa'a Co'i (Delivery Mahar/Dowry), Teka ra Ne’e (Contribution). is still ongoing until now and still maintained by the people of Donggo tribe in the Village of O'o Donggo District of Bima Regency in social life as a form of preservation of their old culture and tradition which has been passed down from generation to generation.